Adult Day Center Use among Older Mexican Americans with Dementia in California and Texas - Angel, Jacqueline L.; Rote, Sunshine M. (Medical Research Archives, 2026)
Background. Dementia is one of the most common causes of disability and dependence in the world and is a frequent reason that older people require supportive living arrangements. New and innovative social policy, in line with Recommendation #10 of the Policy Framework Reducing the Burden of Neurodegenerative Diseases in Europe and Beyond, is vital. The current study offers insights based on dementia care for Latinos in California and Texas, a population with a high incidence of the disease and low resources. Objective. This study investigates how a growing number of Latino families use adult day care services. We focus on California and Texas, the two states with the largest Latino populations of Mexican origin with dual-eligible (Medicare and Medicaid) beneficiaries. Methods. We employ the 2015 Hispanic Established Epidemiologic Studies of the Elderly to compare the socioeconomic characteristics of Mexican Americans 80 and over who are day care service users living with and without dementia in both states (n = 406). Logistic regressions are used to determine the likelihood of participation in adult day care programs in both states by insurance status. Results. Compared to California, restrictive income eligibility requirements in Texas limit participation in adult day care despite a higher need for care. Multivariate analyses reveal that foreign-born dual-eligibles in Texas are particularly dependent on family, to provide dementia caregiving in comparison to the native born; they do not report using adult day health services. Conclusion. The paper ends with a discussion of viable policy options for promoting equity in access to affordable and sustainable adult day health centers as well as other community-based long-term care services in Texas and California. A multi-faceted approach is necessary and must involve all levels of government, as well as private and charitable organizations.